Pengembangan Kewirausahaan Berbasis Potensi Lokal dan Pemberdayaan Masyarakat Terhadap Peningkatan Literasi Ekonomi Rumah Tangga Strategi ABG-C (Academic, Business, Government, and Community) Di PKBM AL-MANAR Medan Sumatera Utara - Wildawati, Meidina; Tahura, T. Lyza; Pentana, Sopi (Jurnal Ekonomi Bisnis Digital, 2022)
This study aims to determine the effect of entrepreneurship development on increasing household economic literacy, to determine the effect of community empowerment on increasing household economic literacy, to find out whether the ABG-C strategy moderates the effect of entrepreneurship development on increasing household economic literacy and to determine whether the ABG-C strategy moderates the effect of community empowerment on increasing household economic literacy. The total population in the study was 110 people, so the saturated sampling technique was used. The analysis technique used is multiple linear regression and MRA.The resultsshowed that the development of entrepreneurship has a positive and significant effect on increasing household economic literacy, community empowerment has a positive and significant effect on increasing household economic literacy, the ABG-C strategy does not moderate the effect of entrepreneurship development on increasing household economic literacy, the ABG-C strategy does not moderate the effect of entrepreneurship development on increasing household economic literacy. ABG-C strategy does not moderates the effect of community empowerment on increasing household economic literacy.